Integrasi Pembumian Pembelajaran Sains Anak Usia dini dengan Pendekatan STEAM di PAUD Mutiara Hati Rinjani - Ida Bagus Alit Arta Wiguna; Ni Luh Drajati Ekaningtyas; Desak Putu Saridewi; Ni Komang Wiasti; Sri Sofiana Amni; I Made Ardika Yasa; Ida Ayu Made Yuni Andari; Ni Made Frescillia Atika; Ni Made Sinta Permata Widari (Dharma Sevanam : Jurnal Pengabdian Masyarakat, 2023)
Science learning for early childhood is very important to develop children's curiosity and understanding of the world around them. Through science learning, children can develop logical thinking skills, observation, and experimentation. The focus of this service is to integrate science learning with STEAM through simple science practices. The purpose of this service is to integrate science grounding with the STEAM Approach and the importance of science learning obtained for early childhood with simple science learning practices. The method used in this service is the counselling method and the simple science practice method. The results of this service are 1). Implement Holistic Learning, 2). Exploring the development of 21st Century Skills, 3) Increasing children's interest in learning science, 4). Active and Fun Learning, 5) Developing Creativity and Innovation in learning.